Representations of Violence in the Eighteenth-Century Pacific - Patel, Sandhya. author. aut Link
IX, 224 p. 11 illus.
Keywords: This book explores representations of the extensive violence that characterised British exploratory and colonising forays into the Pacific Ocean in the long eighteenth century, both between Europeans and Indigenous peoples and amongst Europeans themselves. It explores how navigators, alongside powerful commissioning bodies and editors, depicted violence in manuscripts, published texts, and iconographies, as the British negotiated competing colonial claims to Pacific spaces. In so doing, it identifies recurring and reproductive constructions of violence underpinning legitimizing imperial narratives. Sandhya Patel is Reader in Eighteenth-Century Studies at Université Paul-Valéry Montpellier 3, France.